The enigmatic Calyptophractus retusus (Cingulata: Chlamyphorinae): Distribution and new records outside its range in the Paraguayan Chaco - Thomas Goossen-Lebrón; Maida Bareiro de Bueckert (Mammalogy Notes)
We report a new record of Calyptophractus retusus, a rare species of armadillo, for the Paraguayan Chaco and include photographic records from local media, the iNaturalist platform, and technical reports, counting 11 known records in the country Some of the records presented extend few kilometers the known range of the species in the Paraguayan Chaco.